Topical Combination Delivery of Benzoyl Peroxide and Adapalene Niosomal Gel for Acne Treatment - Shrivastava, Birendra (Asian Journal of Pharmaceutics (AJP), 2019)
Aim and Objective: Adapalene (ADP) is very effective in 0.01% strength, but it causes skin erythema in the applied area. ADP and benzoyl peroxide (BPO) are the most commonly used drugs in treatment of acne. ADP acts as keratolytic agent and BPO acts as potent antibacterial agent, both the drugs are used individually in a cyclic manner. The combination of both drugs if used judiciously can be used to cure mild to moderate acne effectively by acting on pathogenetic site. The successful treatment of acne depends on the maintenance of effective drug concentration levels at the affected site. The main benefit over liposome is that the lipids are replaced by non-ionic vesicles and hence the preparation is totally non-antigenic. Materials and Methods: The non-ionic surfactants like SPANs are obtained from synthetic sources, and hence the quality is maintained same all the time. The ADP was incorporated into niosomes using SPAN 60 and cholesterol was used as a stabilizer. Various ratios of SPAN 60, cholesterol, Stearic acid, BPO, and ADP were tried and optimized. Various process parameters were also optimized for the rotary flask evaporation method. The present study investigates the effect of niosomal coadministration of BPO and ADP in term of in vitro skin retention study and in vivo antiacne effects. These vesicular carriers, because of their improved percutaneous delivery and better skin retention, have proved to be very useful in enhancing therapeutic index of drugs used for tropical diseases. The niosomal dispersion was incorporated into Carbopol gel. The gel was kept for 3 months accelerated stability studies. Results and Discussion: The niosomal dispersion was evaluated for various parameters such as vesicle size, shape, and morphology by transmission electron microscopy. In vitro and in vivo studies were carried out. The drug release pattern from gel was evaluated on the basis of in vitro studies and skin irritation studies on rabbit skin. Conclusion: The in vitro study shows sustained release gel effects whereas the in vivo study shows no signs of irritation on the applied skin area.